TINJAUAN YURIDIS TERHADAP KONTEN KEKERASAN YANG DI SIARKAN TELEVISI MENURUT UNDANG- UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN - Normansyah Normansyah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This study has three objectives, first explaining the condition of the application of material criminal law to Broadcasting Institution showing the violence in television impressions. Secondly to know the role and responsibility of Television Broadcasting Institution showing the impressions containing elements of Violence. The third explains the obstacles to the implementation of Law No. 32 of 2002 on broadcasting is still not effective in preventing the exposure of violent content on television.Furthermore, this research was conducted in Samarinda city of East Kalimantan, with research location at office, Regional Indonesian Broadcasting Commission (KPID), and by collecting data from various literatures and internet sites. The research used is interview, library research (library research). The results of the data analysis are presented descriptively, ie describe, describe, and explain the issues relevant to this research in clear and detailed.  Data analysis technique used is qualitative analysis, that is by analyzing secondary data obtained according to formulation of problem which have been determined. The results showed that television broadcasters and perpetrators in the display of impressions using elements of violence including irregularities to Law No. 32 of 2002 on Broadcasting, but in fact not applied. The obstacle faced is the first, Business Competition. Now the news on television more and more and growing so that the television stations are competing to present exclusive and exclusive news packaging for the public interest.  Television broadcasts are only concerned with the rating, regardless of the impact of broadcast aired for the wider community. Second, Press Freedom. Freedom of the press and freedom of expression are the "powerful stunts" that continue to be used in today's democratic era. There is nothing wrong with both, even we need to appreciate and fight for it. The problem is, we often forget that freedom must be interpreted as a whole. Moreover, freedom must also be implemented with full wisdom and responsibility. Without it, freedom will certainly be problematic and will certainly cause problems. Freedom with intact meaning assumes freedom with limits.